2006
DOI: 10.1038/sj.bjc.6602998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an inflammation-based prognostic score in patients with inoperable gastro-oesophageal cancer

Abstract: There is increasing evidence that the presence of an ongoing systemic inflammatory response is associated with poor outcome in patients with advanced cancer. The aim of the present study was to examine whether an inflammation-based prognostic score (Glasgow Prognostic score, GPS) was associated with survival, in patients with inoperable gastro-oesophageal cancer. Patients diagnosed with inoperable gastro-oesophageal carcinoma and who had measurement of albumin and C-reactive protein concentrations, at the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
234
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 262 publications
(250 citation statements)
references
References 19 publications
10
234
2
4
Order By: Relevance
“…In our study, only five patients had a GPS of 2, with a poor outcome consistent with previous evidence (Crumley et al, 2006;Hwang et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, only five patients had a GPS of 2, with a poor outcome consistent with previous evidence (Crumley et al, 2006;Hwang et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, prognosis for PCR-positive patients was shown to be significantly worse than for PCR-negative patients, and this was in accordance with the recent data of Crumley et al (2006) and Deans et al (2007), who linked inflammation symptoms with adverse prognosis in patients with gastric cancer. However, there are simpler and cheaper methods than qRT-PCR to assess inflammatory parameters.…”
Section: Sirsupporting
confidence: 89%
“…Nevertheless, in Hwang's study, where 402 patients with advanced gastric adenocarcinoma were included, poor GPS depended largely on elevated CRP level other than descending albumin level (Hwang et al, 2011). In another study, Crumley et al (2006) indicated that low albumin was a confounding factor in the GPS scoring system. And Crumley also demonstrated that the development of hypo-albuminemia was secondary to an ongoing systemic inflammatory response and poor cancer specific survival was secondary to the systemic inflammatory response in patients with gastric cancer (Crumley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%